2021
DOI: 10.1101/2021.04.29.441244
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Aerobic Anoxygenic Phototrophic Bacterium Fixes CO2via the Calvin-Benson-Bassham Cycle

Abstract: Aerobic anoxygenic phototrophic bacteria (AAnPB) are presently known as photoheterotrophs, which use light as auxiliary energy and whose growth is dependent on organic carbon (OC). But herein, we reported an unusual AAnPB strain of B3. True AAnPB is this strain because its growth requirement for oxygen and the harbouring specific genes cbb3- and bd-type cytochrome and acsF, and the production of bacteriochlorophyll in AAnPB. The genome showed this isolate had the complete metabolic pathways for the light utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 78 publications
1
5
0
Order By: Relevance
“…S4). This is consistent with the emerging picture of Rhodospirillales AAPs that have Rubisco and the whole Calvin cycle for carbon fixation ( 54 ). There also are taxa without photosynthetic traits that contain a catalytically active Form I Rubisco, as in the case of Acidiphilium iwatense ( Fig.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…S4). This is consistent with the emerging picture of Rhodospirillales AAPs that have Rubisco and the whole Calvin cycle for carbon fixation ( 54 ). There also are taxa without photosynthetic traits that contain a catalytically active Form I Rubisco, as in the case of Acidiphilium iwatense ( Fig.…”
Section: Resultssupporting
confidence: 89%
“…5A ). Indeed, aerobic photosynthesis helps a variety of bacteria to survive in deserts and other extreme, oligotrophic environments ( 54 , 61 ). Ultimately, the distribution pattern and the number of pyrroloquinoline (PQQ)-dependent Q reductases emerged as one of the most widespread traits compensating for the loss of RCs ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Also, the use of RNA quantification instead of DNA may better evidence abundance patterns between phototrophs and chemoautotrophs. Furthermore, our results show that AAnPBs represented ∼8% of total prokaryotes in Counozouls and ∼15% of total prokaryotes in Männikjärve, suggesting they may play a significant role in the C cycle of peatlands as some strains possessing CBB cycle genes can actively fix atmospheric CO 2 (Graham et al, 2018; Tang et al, 2021). Altogether these results show that further work is urgently needed to better quantify the contribution of microorganisms to peatland CO 2 uptake as current estimates based on sole oxygenic phototrophs (Hamard et al, 2021a) may be strongly underestimated.…”
Section: Resultsmentioning
confidence: 84%
“…Potential CO 2 fixation through the CBB cycle also recently emerged in aerobic anoxygenic phototrophic bacteria (AAnPBs). Recent studies found AAnPB strains possessing (and expressing) genes of the CBB cycle (Graham et al, 2018; Tang et al, 2021). Even though CFMs are now well recognized for their role in autotrophic CO 2 fixation in soils, their absolute quantification remains elusive (Liao et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Potential CO 2 fixation through the CBB cycle also recently emerged in aerobic anoxygenic phototrophic bacteria (AAnPBs). Recent studies found AAnPB strains possessing (and expressing) genes of the CBB cycle (Graham et al, 2018; Tang et al, 2021). Even though CFMs are now well recognized for their role in autotrophic CO 2 fixation in soils, their absolute quantification remains elusive (Liao et al, 2023).…”
Section: Introductionmentioning
confidence: 99%